The Incidence Pattern of Electrical Burns at the Department of Plastic Surgery Dr. Soetomo General Academic Hospital, Surabaya, from January 2014 to December 2017 - Merilyne Merilyne; David Sontani Perdanakusuma; Linda Astari (Universitas Airlangga, 2023)
Highlights:1. Electrical burns may progress even when the source has been removed.2. The most common age group to suffer from electrical burns was the 26–35 years old group.3. There was a significant association between electrical burns and the productive age of male employees who work in the private sector. AbstractIntroduction: Burns are direct or indirect damage to the skin tissue and can reach internal organs. This study aimed to investigate the incidence pattern of electrical burn patients at the Department of Plastic Surgery Dr. Soetomo General Academic Hospital, Surabaya, from 1 January 2014 to 31 December 2017, focusing on the age, gender, and occupation aspect of the patients.Methods: This was a descriptive retrospective study evaluating 50 patients treated for electrical burns from 1 January 2014 to 31 December 2017 using the patients’ medical records. The parameters assessed were age, gender, occupation, cause of injury, and annual incident. The data was collected from the medical records Dr. Soetomo General Academic Hospital, Surabaya.Results: Most electrical injuries occurred in May, as many as 12 (24%) patients. There were 49 (98%) male and 1 (2%) female patients. The patients ranged from 8–60 years old, with 17 (34%) patients in the 26-35 age group. 76% of patients were private employees. Work accidents caused approximately 82% of electrical injuries.Conclusion: There was a significant association between electric burns with males at productive age and working as private employees. Many electric accidents occurred while working, especially in May.